A cross-country survey of attitudes toward childbirth technologies and interventions among university students. Issue 3 (June 2019) - Stoll, Kathrin; Edmonds, Joyce; Sadler, Michelle; Thomson, Gill; McAra-Couper, Judith; Swift, Emma M.; Malott, Anne; Streffing, Joana; Gross, Mechthild M.; Downe, Soo
Abstract: Problem & aim: Cultural beliefs that equate birth technology with progress, safety and convenience contribute to widespread acceptance of childbirth technology and interventions. Little is known about attitudes towards childbirth technology and interventions among the next generation of maternity care users and whether attitudes vary by country, age, gender, childbirth fear, and other factors. Methods: Data were collected via online survey in eight countries. Students who had never had children, and who planned to have at least one child were eligible to participate. Findings: The majority of participants (n = 4569) were women (79.3%), and the median age was 22 years. More than half of students agreed that birth technology makes birth easier (55.8%), protects babies from harm (49.1%) and that women have a right to choose a medically non-indicated cesarean (50.8%). Respondents who had greater acceptance of childbirth technology and interventions were from countries with higher national caesarean birth rates, reported higher levels of childbirth fear, and were more likely to report that visual media or school-based education shaped their attitudes toward birth. Positive attitudes toward childbirth technology and interventions were also associated with less confidence in knowledge of birth, and more common among younger and male respondents. Discussion/conclusion: Educational strategies to teach university students about pregnancy and birth in ways that does not frighten them and promotes critical reflection about childbirth technology are needed. This is especially true in countries with high rates of interventions that reciprocally shape culture norms, attitudes, and expectations.